3 UMPSA staff awarded Honorary Ranks under APMM - Saharudin, Ramli (UMPSA, 2024)
GEBENG, 22 July 2024 – Three staff members from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were recently honoured with honorary ranks under the Malaysian Maritime Enforcement Agency (APMM).